APPLICATION OF HYDRAULIC FLOW EQUATION OF EVALUATION OF VARIABLE MASSYDLYA DISTRIBUTION - and (Municipal economy of cities. Series: «Economy science», 2013)
The theoretical equations for estimating the distribution of flow in an inclined section of thin-layer elements.